A think-aloud protocol of the translation process of a scientific text introduction from English to Malay - Gurdial Singh, Kulwindr Kaur (Journal of Modern Languages, 2017)
This study investigates the cognitive processes involved in the translation process of an English language scientific text, hereafter referred to as the source text, into the Malay language, hereafter referred to as the target text, via a think-aloud protocol (TAP). The subject for this study was a Malay lady lecturer from the Biochemistry Department, Faculty of Medicine, University of Malaya, who is also a part-time, experienced translator. The technique (TAP) involves asking the subject to think aloud or articulate everything that went on in her mind while she was translating.